Kecerdasan Emosional dan Korelasinya terhadap Kedisiplinan Belajar Peserta Didik di SMP Negeri 3 Semarang - Muhammad Ja’far Musthafa; Hida yatus Sholihah (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2024)
The research is conducted to find out the relationship between the emotional intelligence of students and the discipline of studying Islamic education in class IX at SMP Negeri 3 Semarang in the 2022/2023 academic year.This type of research was correlation research or relationship research and the research method all used was quantitative. Collecting data in this study using a questionnaire or questionnaire. The population in this study were all students of class IX, which totaled 256 students. While the sample of this study used a simple random sampling technique. How to determine the number of samples using the Slovin formula with an error rate of 5%, it can be seen that the sample is 73 students.Based on data analysis and calculations, it shows that the level of emotional intelligence of class IX students at SMP Negeri 3 Semarang is mostly in the medium category, namely 44 students (60.3%), 17 students (23.3%), and 12 high students. students (16.4%). The majority of the level of discipline in learning Islamic education subject class IX at SMP Negeri 3 Semarang is in the medium category, namely 50 students (68.5%), low 13 students (17.8%), and high 10 students (13.7%). Based on the test results using the product moment correlation from Pearson, it is known that the correlation between the two variables is (0.03) <0.05. So it can be said that the two variables are correlated, and the relationship between the two variables is (0.341) classified as low correlation. So it can be said, the relationship between emotional intelligence with the discipline of learning PAI subject in class IX at SMP Negeri 3 Semarang has a significant relationship and the hypothesis is accepted (Ha).Â